2012
DOI: 10.1002/cne.23026
|View full text |Cite
|
Sign up to set email alerts
|

Developmental expression of cell recognition molecules in the mushroom body and antennal lobe of the locust Locusta migratoria

Abstract: We examined the development of olfactory neuropils in the hemimetabolous insect Locusta migratoria with an emphasis on the mushroom bodies, protocerebral integration centers implicated in memory formation. Using a marker of the cyclic adenosine monophosphate (cAMP) signaling cascade and lipophilic dye labeling, we obtained new insights into mushroom body organization by resolving previously unrecognized accessory lobelets arising from Class III Kenyon cells. We utilized antibodies against axonal guidance cues,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 109 publications
1
7
0
Order By: Relevance
“…Moreover, Neurobiotin labeling of axotomized olfactory fibers could clearly ascribe the recovery of antennal lobe volume to regenerated axons. Intriguingly, regenerating olfactory receptor axons express embryonic cell surface molecules indicative of reacquisition of a developmental mode [37], [13]. The observed time course of degeneration and subsequent regeneration is comparable to what has been shown in other insect sensory systems such as deafferented cercal fibers in the cockroach and auditory afferents in the grasshopper [38][40].…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, Neurobiotin labeling of axotomized olfactory fibers could clearly ascribe the recovery of antennal lobe volume to regenerated axons. Intriguingly, regenerating olfactory receptor axons express embryonic cell surface molecules indicative of reacquisition of a developmental mode [37], [13]. The observed time course of degeneration and subsequent regeneration is comparable to what has been shown in other insect sensory systems such as deafferented cercal fibers in the cockroach and auditory afferents in the grasshopper [38][40].…”
Section: Discussionsupporting
confidence: 74%
“…aegypti . The antibody, which was recently used to detect Sema1a expression in grasshoppers [17], was found to specifically recognize Aae Sema1a in the developing brain, as assayed by the lack of brain staining assessed in Ae. aegypti sema1a knockdown animals (see below).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, graded Sema1a expression in the antennal lobe is required for the proper targeting of projection neuron dendrites into the antennal lobe [13]. Although Sema1a expression has been detected in the developing Locusta migratoria olfactory system [17], the function of Sema1a during pupal olfactory development has not yet been assessed in insects other than D. melanogaster . Our recent studies have revealed differences between D. melanogaster and Ae.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of many guidance molecules tends to decrease after development, though expression appears to be maintained in select areas. In particular, areas with high levels of plasticity, such as the hippocampus in mammals (Giger et al, 1998;Pascual, Pozas, & Soriano, 2005;Sahay et al, 2005) or the MBs in invertebrates (Eickhoff & Bicker, 2012;Maynard et al, 2007), continue to express developmental guidance molecules, including the Sema proteins, into adulthood. Experiments in mammals indicate that these developmental guidance proteins are important regulators of adult neuroplasticity, pruning axons, eliminating synapses, and reducing spine density and size in order to constrain plasticity in more mature circuits (Boggio et al, 2019;Lee et al, 2012;Riccomagno & Kolodkin, 2015;Tran et al, 2009).…”
Section: Sema1a Signaling In the Adultmentioning
confidence: 99%
“…The expression patterns of the Semas and Plexins have been described most thoroughly during development, but both continue to be expressed in some CNS regions into adulthood. Semas can be found in the adult CNS in both vertebrates (Duan et al, ; Giger, Pasterkamp, Heijnen, Holtmaat, & Verhaagen, ) and invertebrates (Maynard, McCarthy, Sheldon, & Horch, ), typically in areas of high plasticity such as the hippocampus (Sahay et al, ) and the mushroom bodies (Eickhoff & Bicker, ; Maynard et al, ). Plexins have also been described in the adult CNS in vertebrates (Gutekunst, Stewart, & Gross, ; Saha, Ypsilanti, Boutin, Cremer, & Chedotal, ; Usui, Taniguchi, Yokomizo, & Shimizu, ), and invertebrates (Yoo, ) though less is known about Plexin distribution at this stage.…”
Section: Introductionmentioning
confidence: 99%